465. Microbial Removal Efficacy of a Novel Nonantimicrobial Hand Soap. (26th November 2018) - Edmonds-Wilson, Sarah; Duley, Collette; Mays-Suko, Patricia; Tian, Kegui; Bingham, James
Abstract: Background: The CDC Hand Hygiene Guidelines recommend washing hands with soap when hands are visibly soiled. Pending changes to the United States healthcare antiseptic regulations are decreasing the availability of antimicrobial soap active ingredients making it important to understand key performance differences across soap types. The purpose of this study was to investigate the germ removal properties of a novel, nonantimicrobial soap exhibiting improved interfacial tension properties, a measure of the interaction of the soap with skin. Methods: The novel nonantimicrobial soap was compared with a control nonantimicrobial soap. In study 1, the soaps were tested according to ASTM E2755 to determine reduction of Serratia marcescens after one use where 5 mL of soap was applied to dry hands, lathered 30s and rinsed 30s ( N = 12). Studies 2 and 3 compared the products under more realistic test conditions, including a more relevant healthcare pathogen, more realistic product application and in study three skin condition representative of healthcare worker skin. The second study compared the novel soap and the control soap for Staphylococcus aureus removal using ASTM E2755 with 1.8 mL of soap applied to dry hands, lathered for 30s and rinsed for 10s ( N = 12). The third study used an ex vivo skin model of dry, irritated human skin to evaluate S. aureus removal. Statistical comparisons between soaps were made using a paired t-test (α = 0.05). Results: In all three studies, the novel nonantimicrobial soap was superior to the control soap for bacteria removal. In study 1, the novel soap achieved a 2.26 log10 reduction compared with a 1.70 log10 reduction for the control soap ( P < 0.0001). In studies 2 and 3, the nonantimicrobial soap achieved log10 reductions that were 0.34 ( P = 0.0236) and 0.53 ( P = 0.005) greater than the control soap, respectively. Conclusion: This study indicates that a nonantimicrobial soap can achieve a high level of microbe removal (>99%) on skin. Additionally, product formulation appears to impact the microbial removal properties of nonantimicrobial soap on both healthy human subjects, and on dry irritated human skin. Therefore, this novel soap may be a good option in a high-frequency hand hygiene environment such as healthcare. Disclosures: S. Edmonds-Wilson, GOJO Industries: Employee, Salary. K. Tian, GOJO Industries: Employee, Salary. J. Bingham, GOJO Industries: Employee, Salary.